Core Strategy of Islamic Religious Education Teachers in Forming Student Piety Through Contextual and Meaningful Learning at Madrasah Tsanawiyah Al-Munawaroh Tangerang - Cecep Maman Hermawan; Sayyida Nafisa; Muhammad Randy Islami; Elfia Zahra; Hasbi Ramadhan; Chairil Raddin; Okta Rosfiani (Journal of Research in Islamic Education, 2025)
Islamic Religious Education (PAI) learning is often trapped in a textual approach that is less effective in forming students' holistic piety. Integration of contextual and meaningful learning is a potential solution, but the strategic role of PAI teachers as key actors has not been explored in depth. The purpose of this study was to find the core strategies of PAI teachers in designing and implementing contextual and meaningful learning to form students' piety. Qualitative research was used as a research approach, with a case study design in Tangerang. Data collection through in-depth interviews with 6 PAI teachers, 25 students, 1 Curriculum Deputy, participant observation, and document studies. Data analysis used an interactive model with source triangulation. Key research findings identified four core strategies: 1) Contextualization of religious values ​​with students' socio-ecological realities (e.g., integration of local wisdom in Akidah Akhlak material; 2) Design of meaningful experiential learning based on projects (e.g., Ecological Dhikr, Literacy Hijrah); 3) Modeling contextual piety (living curriculum) through behavioral examples; 4) Structured reflection based on Qur'anic values ​​(Qur'anic Mirroring). The impact of this strategy is proven to form holistic piety including individual (consistency of worship), social (empathy, collaboration), and ecological (environmental concern) aspects, with social piety as the most responsive domain (80%). The implications of this finding theoretically strengthen the Contextual Spirituality Pedagogy model through an integrative cycle of contextualization-experience-reflection, practically: Providing an operational framework for teachers and schools in designing transformative learning based on local context.